2003
DOI: 10.1038/sj.bmt.1704022
|View full text |Cite
|
Sign up to set email alerts
|

Central venous catheter pinch-off and fracture: recognition, prevention and management

Abstract: Summary:The so-called pinch-off syndrome is observed in up to 1% of all central venous catheters (CVCs), and is a valuable warning prior to fragmentation, which occurs in approximately 40% of the respective cases. As long-term indwelling CVCs are used with increasing frequency, this paper describes the necessity of pinch-off monitoring following the experiences of a case study and a review of the current literature on this specific topic in order to point out preventive practice guidelines.Besides easy prevent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
8

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 28 publications
0
33
0
8
Order By: Relevance
“…While the 'pinch-off syndrome' only occurs in about 1% of patients with a CVC, up to 40% of these cases develop fragmentation and subsequent embolization of the catheter tip into the central vascular system. 8,9 Catheter obstructions can also be due to a non-thrombotic internal occlusion, such as precipitation of medications or parenteral nutrition constituents. Obstructions caused by precipitation of medications with a low pH and those due to calcium phosphate crystals can be treated with 0.1% hydrochloric acid (HCl).…”
Section: Types Of Catheter Obstructionmentioning
confidence: 99%
“…While the 'pinch-off syndrome' only occurs in about 1% of patients with a CVC, up to 40% of these cases develop fragmentation and subsequent embolization of the catheter tip into the central vascular system. 8,9 Catheter obstructions can also be due to a non-thrombotic internal occlusion, such as precipitation of medications or parenteral nutrition constituents. Obstructions caused by precipitation of medications with a low pH and those due to calcium phosphate crystals can be treated with 0.1% hydrochloric acid (HCl).…”
Section: Types Of Catheter Obstructionmentioning
confidence: 99%
“…It is well known that 'pinch-off' syndrome can lead to fracture of catheters. 4,9,14,15 'Pinch-off' is thought to occur when acatheter is inserted into the subclavian vein too medially via ap ercutaneous Seldinger approach and becomes compressed between the first rib, clavicle and costoclavicular ligament. All TIVADs in this cohort were inserted by open cut-down; af ew were placed directly in the subclavianvein, but into the middle or lateral third, well away from thec ostoclavicular ligament.…”
Section: Leakagementioning
confidence: 99%
“…This leads to catheter fracture with time. It is observed in approximately 40% of catheter embolizations in adult patients (12,13). In our series, pinch-off syndrome caused catheter fracture and embolism in three of five patients, all of whom were adults.…”
Section: Discussionmentioning
confidence: 90%
“…Fisher and Ferreyro reported that the combined rate of pulmonary thromboembolism, perforation of the right ventricle, cardiac arrest, and death was 71% (13). This high mortality and complication rate might be attributed to the use of rigid materials in the early 1970s.…”
Section: Discussionmentioning
confidence: 99%